Rhodanine hydrolysis leads to potent thioenolate mediated metallo-β-lactamase inhibition. - Brem, J; van Berkel, S; Aik, W; Rydzik, A; Avison, M; Pettinati, I; Umland, K; Kawamura, A; Spencer, J; Claridge, T; McDonough, M; Schofield, C (Nature Publishing Group, 2014)
The use of β-lactam antibiotics is compromised by resistance, which is provided by β-lactamases belonging to both metallo (MBL)- and serine (SBL)-β-lactamase subfamilies. The rhodanines are one of very few compound classes that inhibit penicillin-binding proteins (PBPs), SBLs and, as recently reported, MBLs. Here, we describe crystallographic analyses of the mechanism of inhibition of the clinically relevant VIM-2 MBL by a rhodanine, which reveal that the rhodanine ring undergoes hydrolysis to give a thioenolate. The thioenolate is found to bind via di-zinc chelation, mimicking the binding of intermediates in β-lactam hydrolysis. Crystallization of VIM-2 in the presence of the intact rhodanine led to observation of a ternary complex of MBL, a thioenolate fragment and rhodanine. The crystallographic observations are supported by kinetic and biophysical studies, including (19)F NMR analyses, which reveal the rhodanine-derived thioenolate to be a potent broad-spectrum MBL inhibitor and a lead structure for the development of new types of clinically useful MBL inhibitors.